2015
DOI: 10.1038/nm.3993
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic lethal targeting of oncogenic transcription factors in acute leukemia by PARP inhibitors

Abstract: Acute myeloid leukemia (AML) is mostly driven by oncogenic transcription factors, which have been classically viewed as intractable targets using small molecule inhibitor approaches. Here, we demonstrate that AML driven by repressive transcription factors including AML1-ETO and PML-RARα are extremely sensitive to Poly (ADP-ribose) Polymerase (PARP) inhibitor (PARPi), in part due to their suppressed expression of key homologous recombination genes and thus compromised DNA damage response (DDR).In contrast, leuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
166
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(171 citation statements)
references
References 65 publications
5
166
0
Order By: Relevance
“…A combination approach may also be of benefit. In preclinical models of AML, PARP inhibitors are most effective in killing AML cells in which the HDR repair mechanism is also impaired [56]. Thus, it will be interesting to investigate the sensitivity of IDH1/2-and TET2-mutant AML to PARP inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…A combination approach may also be of benefit. In preclinical models of AML, PARP inhibitors are most effective in killing AML cells in which the HDR repair mechanism is also impaired [56]. Thus, it will be interesting to investigate the sensitivity of IDH1/2-and TET2-mutant AML to PARP inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data revealing the requirement for DOT1L activity in HOXA-overexpressing acute myeloid leukemia 21 suggest that pharmacological DOT1L inhibition might also have therapeutic benefit in T-ALL. In addition, recent evidence from in vitro and animal models suggests that combined inhibition of glycogen synthase kinase and poly(ADP-ribose) polymerase effectively suppresses growth of chemoresistant HOXA-overexpressing acute myeloid leukemia, 44 suggesting a similar potential avenue of investigation in HOXA Pos T-ALL.…”
Section: A B C Dmentioning
confidence: 99%
“…Strikingly, the presence of an early thymic precursor-like immunophenotype was associated with marked outcome differences within the HOXA-positive group (5-year overall survival 31.2% in HOXA-positive early thymic precursor versus 66.7% in HOXA-positive non-early thymic precursor, P=0.03), but not in HOXA-negative cases (5-year overall survival 74.2% in HOXA-negative early thymic precursor versus 57.2% in HOXA-negative non-early thymic precursor, P=0. 44). Multivariate analysis further revealed that HOXA positivity independently affected eventfree survival (P=0.053) and relapse risk (P=0.039) of chemoresistant T-cell acute lymphoblastic leukemia.…”
mentioning
confidence: 91%
“…Leukemic cells driven by the oncofusion genes, AML1-ETO and PML-RARα, are sensitive to PARP inhibition whereas cells harbouring MLL-AF9 translocation are resistant [8]. …”
Section: Resultsmentioning
confidence: 99%
“…More importantly, we showed for the first time that HoxA9 can activate a potential DNA repair back-up pathway. PARPi in combination with pharmacological inhibitors of HOXA9 may represent a novel avenue for tailored therapeutic targeting of the aggressive MLL leukaemia [8].…”
Section: Discussionmentioning
confidence: 99%